The Virtue Role in the Sustainability of Architecture - JaafarHasan, Alaa; Saadoon Salman Almaamori, Abdullah (International Journal of Engineering and Technology, 2018)
Until man reaches the moderation, it must reform itself and its activities as the infrastructure of society. Since his inception on the basis of moral virtues It also help him to move towards society, thus achieving human development which in turn achieves sustainability. The research addressed virtue as an integral part of morality, from it began the teachings of religion and showed the relationship between him and his environment Based on the concept of moderation to achieve sustainability.the Search attempt to discuss the absence clear imagination of virtue concept and its role in architecture sustainability, so The research aims to clarity the role of the concept of virtue in the permanence of the architecture and its survival on the assumption that virtue has a role in the sustainability of architecture. To achieve this aim the research used Inductive methodology (descriptive, analytical) through election samples and Test, finally Take virtue into consideration in the design process Contributes to the sustainability of the building Conversely in the event of negligence, it may lead to outbreaks of vices and the factors of violence and theft that cause the abandonment of the building is The most important results.Â